The Relationship between Verbal Bullying and Low Self-Esteem of Students at SMA Muhammadiyah 3 Jember - Lidya Nanda Nadilla Putri; Yeni Suryaningsih; Ns. Komarudin (Penerbit Hellow Pustaka, 2025)
Bullying is unpleasant behavior carried out by the social environment towards individuals. In Indonesia, cases of bullying, especially verbal bullying, are widely reported by various surveys and institutions such as GSHS and KPAI. Bullying can cause various psychological problems, including low self-esteem in teenagers. This research aims to determine the relationship between verbal bullying and low self-esteem in students at SMA Muhammadiyah 3 Jember. This research uses a cross-sectional study design with a student population. Muhammadiyah High School 3 Jember. Data was collected through a questionnaire that included questions about experiences of verbal bullying and level of self-esteem. Data analysis was carried out using statistical correlation tests to see the relationship between verbal bullying and low self-esteem. The research results showed that there was a significant relationship between verbal bullying and low self-esteem among students at SMA Muhammadiyah 3 Jember. Students who experience verbal bullying tend to have lower self-esteem compared to those who do not experience verbal bullying. Verbal bullying has a significant negative impact on students' self-esteem. Therefore, there needs to be more effective intervention from schools and parents to prevent and handle bullying cases, as well as providing psychological support to victims to increase their self-esteem